Pengaruh Fitur Augmented Reality (AR) dan Nilai Pelanggan pada Kepuasan Pengguna Layanan Transportasi Online: (Studi Kasus pada Pengguna Aplikasi Transportasi Online di Kota Medan) - Supriadi Siagian; Rila Maufira; Bertha Nerphy Siahaan; Muridha Hasan (MAMEN: Jurnal Manajemen, 2026)
This study aims to analyze the influence of Augmented Reality (AR) features on user satisfaction in online transportation services and to examine the mediating role of customer value among users in Medan City. A quantitative survey approach was employed in this study. The sample consisted of 120 active users of online transportation services in Medan City, selected using purposive sampling. Data were collected through a structured questionnaire and analyzed using multiple linear regression and the Sobel mediation test. The findings reveal that AR features have a positive and significant effect on customer value and user satisfaction. Customer value also has a significant positive effect on user satisfaction and is proven to partially mediate the relationship between AR features and user satisfaction. These results indicate that the implementation of AR features enhances user satisfaction primarily through increased perceived customer value. The regression coefficients show that AR features (X₁) have a value of 0.328, while customer value (X₂) has a value of 0.415, suggesting that both variables play an important role in shaping user satisfaction. The coefficient of determination (R²) of 0.587 indicates that the research model has a relatively strong explanatory power. This study is limited to Medan City and a relatively small sample size, which may affect the generalizability of the findings. Future research is recommended to expand the study area and include additional variables such as trust and user experience to enrich the research model.